Arthroscopic Repair of an Anteroinferior Capsular Tear in the Shoulder of a Throwing Athlete - Thomas E. Moran MD; Brian McGuire PT; F. Winston Gwathmey MD (SAGE Publishing, 2023)
Background: Anterior capsular tears are often associated with traumatic glenohumeral instability episodes; however, there are not many previous descriptions in the literature without occurrence of frank dislocation. This video will discuss the presentation of a throwing athlete with an anteroinferior capsular tear in his dominant shoulder who underwent successful arthroscopic repair. Indications: Based on the patient's clinical symptoms, magnetic resonance imaging arthrogram findings, and failure to return to play despite attempts at conservative management, he was determined to be a candidate for arthroscopic repair. Technique Description: Arthroscopic repair consisted of reapproximation of the avulsed capsular tissue to its attachment point medially using suture anchors in the glenoid and a side-to-side repair of the mid-substance extension of the capsular split. Results: Arthroscopic repair of the anteroinferior capsular tear allowed the patient to return to his previous level of sport. Discussion/Conclusion: In the present case and a previous case series, surgical repair of anterior capsular tears, whether arthroscopic or open, can yield good results in throwing athletes aiming to return to prior levels of performance. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.